PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN PEMBUATAN BUSANA INDUSTRI KELAS XI DI SEKOLAH MENENGAH KEJURUAN - Kamsia, Nur Cahaya (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2025)
The purpose of this study was to find out: (1) the implementation of blended learning for Class XI Fashion Design students, (2) the learning outcomes of Class XI Fashion Design students, (3) the effect of implementing blended learning on student learning outcomes for Class XI Fashion Design at SMK Negeri 2 Tolitoli. This research is a quantitative research that is ex-post facto. The population in this study were 100 class XI Fashion Design students, 50 samples were determined using the Slovin formula. Data collection uses questionnaires and documentation. Instrument trials were conducted on 30 students outside the sample. The results of the validity test obtained 28 valid items and 4 invalid items. The hypothesis test uses the product moment correlation which is preceded by the requirements analysis test, namely the normality and linearity tests. Reliability test with alpha cronbach with a coefficient value of 0.808. The results showed that (1) the blended learning model was in the moderate category with a relative frequency of 48% (2) the learning outcomes of industrial fashion subjects were in the high category with a relative frequency of 56% (3) there was a positive and significant influence between the blended learning model on learning outcomes for industrial fashion subjects with a value of rcount = 0.587 > rtable 0.279 and a determinant value (R2) of 0.344 which means that the blended learning model variable contributes 34.4% to the learning outcome variable